Patients’ perception of chemotherapy side effects: Expectations, doctor–patient communication and impact on quality of life – An Italian survey - Lorusso, Domenica; Bria, Emilio; Costantini, Anna; Di Maio, Massimo; Rosti, Giovanni; Mancuso, Annamaria (European journal of cancer care, 2017)
Chemotherapy side effects (CSE) have a strong impact on patients’ quality of life (QOL). To assess patient perceptions of CSE, their impact on QOL and doctor–patient communication regarding these aspects, a survey was conducted among Italian cancer patients. Patients at least 18 years of age, who received chemotherapy, were administered a dedicated questionnaire to assess their point of view on five domains: expectations about CSE and impact on QOL; doctor–patient communication about CSE; treatments to reduce the impact of CSE; sexual life; family relationships/activities and employment. A total of 761 patients participated. CSE had a considerable impact on patient QOL. Nausea/vomiting was the most feared adverse effect before initiating chemotherapy and the one most commonly experienced during treatment. Patients generally reported good doctor–patient communication regarding information about CSE. In almost all cases, the oncologists prescribed an antiemetic treatment, but the incidence of nausea/vomiting was high. Cancer and CSE severely affected sexual life, daily activities and employment. CSE had a strong negative impact on QOL. Good doctor–patient communication is essential. Improving antiemetic strategies may improve QOL. Doctors’ ability to inform patients about delicate issues, such as the impact of CSE on sexual life, needs to be improved.